2001
DOI: 10.1128/aem.67.2.561-568.2001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Extensive Resistance Gene Transfer among Bacteroides spp. and among Bacteroides and Other Genera in the Human Colon

Abstract: Transfer of antibiotic resistance genes by conjugation is thought to play an important role in the spread of resistance. Yet virtually no information is available about the extent to which such horizontal transfers occur in natural settings. In this paper, we show that conjugal gene transfer has made a major contribution to increased antibiotic resistance in Bacteroides species, a numerically predominant group of human colonic bacteria. Over the past 3 decades, carriage of the tetracycline resistance gene, tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
375
1
7

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(393 citation statements)
references
References 54 publications
10
375
1
7
Order By: Relevance
“…Conjugative transposons have been largely responsible for the spread of tetracycline and erythromycin resistance in clinical isolates of Bacteroides (250). Fifty years ago, tetracycline resistance was almost nonexistent in this genus (103).…”
Section: Mobile Genetic Elements In Bacteroidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Conjugative transposons have been largely responsible for the spread of tetracycline and erythromycin resistance in clinical isolates of Bacteroides (250). Fifty years ago, tetracycline resistance was almost nonexistent in this genus (103).…”
Section: Mobile Genetic Elements In Bacteroidesmentioning
confidence: 99%
“…Conjugative transposons have a mechanism of excision and integration that resemble some features of both plasmids and bacteriophage (231). Conjugative transposons are practically ubiquitous among the Bacteroides: over 80% of Bacteroides strains contain at least one conjugative transposon (250).…”
Section: Mobile Genetic Elements In Bacteroidesmentioning
confidence: 99%
“…Studies have shown that several antibiotic resistance genes are stably maintained in the GI tract once they are acquired (Shoemaker et al, 2001). These genes are often carried on conjugative elements and, under selection pressure, they have the potential to be transferred between different species within the densely populated gut microbial community.…”
Section: Impact Of Antibioticsmentioning
confidence: 99%
“…Escherichia coli and Bacteroides and Enterococcus spp. have been used to monitor the flow and persistence of antibiotic resistance determinants within and between intestinal ecosystems (1,8,22,23,28,29). M. elsdenii is a common anaerobe in the intestinal tracts of both ruminant and nonruminant mammals, including humans.…”
mentioning
confidence: 99%